Patients' and Nurses' Experiences and Perceptions of Remote Monitoring of Implantable Cardiac Defibrillators in Heart Failure: Cross-Sectional, Descriptive, Mixed Methods Study - Liljeroos, Maria; Thylén, Ingela; Strömberg, Anna (JMIR Publications, 2020)
BackgroundThe new generation of implantable cardioverter-defibrillators (ICDs) supports wireless technology, which enables remote patient monitoring (RPM) of the device. In Sweden, it is mainly registered nurses with advanced education and training in ICD devices who handle the arrhythmias and technical issues of the remote transmissions. Previous studies have largely focused on the perceptions of physicians, and it has not been explored how the patients' and nurses' experiences of RPM correspond to each other. ObjectiveOur objective is to describe, explore, and compare the experiences and perceptions, concerning RPM of ICD, of patients with heart failure (HF) and nurses performing ICD follow-up. MethodsThis study has a cross-sectional, descriptive, mixed methods design. All patients with HF and an ICD with RPM from one region in Sweden, who had transitioned from office-based visits to implementing RPM, and ICD nurses from all ICD clinics in Sweden were invited to complete a purpose-designed, 8-item questionnaire to assess experiences of RPM. The questionnaire started with a neutral question: "What are your experiences of RPM in general?" This was followed by one positive subscale with three questions (score range 3-12), with higher scores reflecting more positive experiences, and one negative subscale with three questions (score range 3-12), with lower scores reflecting more negative experiences. One open-ended question was analyzed with qualitative content analysis. ResultsThe sample consisted of 175 patients (response rate 98.9%) and 30 ICD nurses (response rate 60%). The majority of patients (154/175, 88.0%) and nurses (23/30, 77%) experienced RPM as very good; however, the nurses noted more downsides than did the patients. The mean scores of the negative experiences subscale were 11.5 (SD 1.1) for the patients and 10.7 (SD 0.9) for the nurses (P=.08). The mean scores of the positive experiences subscale were 11.1 (SD 1.6) for the patients and 8.5 (SD 1.9) for the nurses (P=.04). A total of 11 out of 175 patients (6.3%) were worried or anxious about what the RPM entailed, while 15 out of 30 nurses (50%) felt distressed by the responsibility that accompanied their work with RPM (P=.04). Patients found that RPM increased their own (173/175, 98.9%) and their relatives' (169/175, 96.6%) security, and all nurses (30/30, 100%) answered that they found RPM to be necessary from a safety perspective. Most patients found it to be an advantage with fewer office-based visits. Nurses found it difficult to handle different systems with different platforms, especially for smaller clinics with few patients. Another difficulty was to set the correct number of alarms for the individual patient. This caused a high number of transmissions and a risk to miss important information. ConclusionsBoth patients and nurses found that RPM increased assurance, reliance, and safety. Few patients were anxious about what the RPM entailed, while about half of the nurses felt distressed by the responsibility that accompanied their work with RPM. To increase nurses' sense of security, it seems important to adjust organizational routines and reimbursement systems and to balance the workload.